Pengaruh motivasi, persepsi dan sikap terhadap keputusan pembelian kembali smartphone - WIBISONO SOEDIONO (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to examine motivation, perception, learning and attitude have influence to repeat purchase. Sample used in this research were 100 respondents. Sample selected based on purposive sampling method. The statistical methods used in this research are multiple regression. Result of this research showed that motivation, perception and attitude have influenced to repeat purchase. The research suggests that marketers should be pay attention to the factors that influence consumer purchasing decisions. Marketer are also should look at the needs of the market so that marketer can create a product that consumers need.